THE FLIGHT OF HAGAR ACCORDING TO JOSEPHUS - Begg, Christopher (Revista Hermenêutica (descontinuada), 2008)
RESUMO Este artigo apresenta uma leitura detalhada deste eventode acordo com Ant. 1.186-190(191a), do escopo de Agarem relação a uma Vorlage (Gen. 16 ) e a tradução judaica(Philo e Gen. Rab. 45). Josefo está mais perto de Gênesis 16a este respeito do que com outras fontes. Josefo parafraseiao texto bíblico enquanto que Philo e Gênesis Rabbah alegorizaa história de Agar. ABSTRACT This essay offers a detailed reading of Josephus’account, in Ant. 1.186-190(191a), of Hagar’s flight in relationboth to its biblical Vorlage (Genesis 16 in its various ancienttext-forms) and the wider early Jewish tradition (Philo andGen. Rab. 45 in particular). Among the essay’s findings arethat Josephus’ version streamlines the Genesis 16 story, whilealso attempting to resolve various problems posed by this andretouching the source portrayal of the chapter’s characters.In comparison with other early Jewish treatments of Genesis16, Josephus’ handling stands out as a rather extendedparaphrase of the biblical narrative, that, as such, contrastswith the atomistic approach to the biblical data adopted byPhilo and Genesis Rabbah, just as it eschews the former’sthoroughgoing allegorization of Hagar’s story.